(untitled) (The Review of Diabetic Studies, 2025)
This research aims to study the effect of training on effective communication techniques in improving patient and family satisfaction with field ambulance services. Effective communication between paramedics and patients is a key component of quality emergency care, as it directly impacts patients’ levels of confidence, comfort, and overall satisfaction with the service provided. The study relied on a descriptive analytical approach, with data collected from a sample of (200) participants comprising paramedics, patients, and their families. A standardized questionnaire was used to measure the impact of communication technology training programs on improving the quality of interaction, understanding patient needs, and raising satisfaction with field ambulance services. The results showed that training in effective communication skills significantly contributes to enhancing empathy, clarity, and professionalism among ambulance personnel, which positively impacts patient and family satisfaction. The study concludes that investing in ongoing training in communication skills is a key factor in improving the quality of pre-hospital care, and recommends incorporating modules dedicated to developing communication skills into field paramedic training programs.